Assessment of the impact of reconstitution therapies—cladribine tablets and alemtuzumab—on the atrophy progression among patients with relapse-remitting multiple sclerosis - Aleksandra Pogoda-Wesołowska; Ignacy Stachura; Arkadiusz Zegadło; Marzena Maciągowska-Terela; Karolina Sobolewska; Aleksander Dębiec; Jacek Staszewski; Adam Stępień (Frontiers in Neuroscience)
IntroductionImmune reconstitution therapies (IRT) are highly effective therapies for multiple sclerosis (MS). Among IRT, we can distinguish partially selective therapies such as cladribine in tablets (CLAD) and non-selective therapies, which include alemtuzumab (ALEM). Today, it is known that these therapies are effective in controlling the relapse activity of the disease and the progression of clinical disability, which has been proven both in clinical trials and in real world evidence (RWE). However, there is a lack of data assessing the effect of IRT on the neurodegenerative process, which is intensified in patients with MS. The aim of the study was to assess the effect of IRT treatment on the degree and pattern of brain atrophy in patients with MS during 3 years of observation.MethodsPatients with relapsing-remitting MS (RRMS) treated with CLAD and ALEM were retrospectively recruited for the study. Demographic, clinical, and magnetic resonance imaging (MRI) data were collected at 4 time points: before the treatment and one, two, and three years after the treatment. MRI examinations were analyzed volumetrically using Freesurfer software. Global and regional changes in atrophy were assessed by calculating percentage changes in volume between time points. Results of drug groups were compared with each other.ResultsAfter 3 years of follow-up, statistically significant differences between groups were observed in hippocampus [p < 0.01] and amygdala volume changes [p < 0.01]. Ventral diencephalon atrophy was noted in both groups. On the other hand, in both groups, no significant atrophy of white and grey matter was noted. In addition, an increase in the thalamus volume was observed.DiscussionIn the studied groups, IRT therapies were shown to slow down the atrophy process in MS patients to a similar extent. These therapies may play a neuroprotective role by increasing the volume of the thalamus and hippocampus. The study was limited by the small number of both groups. Therefore, further studies are needed to fully assess the effect of reconstitution therapies on neurodegenerative processes in patients with RRMS.